To study the production viability of bio-briquette from oil palm decanter cake - Siti Farhana, Haron (2012)
Being among of the largest palm oil producer, Malaysia also produces large quantities of palm oil biomass such as empty fruit bunch (EFB), palm oil mill effluent (POME), palm kernel cake (PKC), decanter cake and palm shell. Due to the large of waste production, there should be a way to reuse this waste. Generally, most of oil palm biomass can be used as combustion fuel. This study is to produce the decanter cake as bio-briquettes. Decanter cakes are very difficult for storing, handling and burning because of the high moisture content levels in the residue and when associated with the organic contents in the decanter cakes, it will cause air pollution and exert polluted gaseous like ammonia gaseous. Utilization of palm oil decanter cake will improve the environment because the disposal of sludge solid waste will increase the Biochemical Oxygen Demand (BOD) of the land. The testing that been done moisture content analysis, volatile matter and ash content analysis, calorific value analysis and density testing. In order to produce the briquettes from the decanter cake, the raw material is dried at the temperature of 105oC for 12 hours using oven in order to get rid the moisture. After that, the dry decanter cake will be grinding to make it into smaller size and separate into three class of sizes which is small, medium, and large to see the effect of the particle sizes. The briquetting process is done by using hydraulic press. In order to make the DC briquette more compact and and reduce the ash content of DC briquette, the raw material is mix with sawdust. Apart from that, DC briquette is compare to the sawdust briquette from Yoltan and pellet rice straw. As conclusion, particle sizes does not really affect the moisture content, volatile matter, ash content and the calorific value of the decanter cake since the raw material is been dry at the same temperature. In this study, the DC briquette can be produce by using hydraulic press and it is could be used as renewable energy in producing solid fuels.